2003
DOI: 10.1161/01.cir.0000055188.83694.b3
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Association of C-Reactive Protein With Adiponectin in Blood Stream and Adipose Tissue

Abstract: Background-High-sensitive C-reactive protein (hs-CRP) is a well-known risk factor for coronary artery disease (CAD).Recently, we have demonstrated that adiponectin served as an antiatherogenic plasma protein which was secreted specifically from adipocytes. The present study investigated the association between adiponectin and CRP in the blood stream and adipose tissue. Methods and Results-We studied a total of 101 male patients, 71 of whom had angiographically documented coronary atherosclerosis. As a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
467
12
24

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 753 publications
(554 citation statements)
references
References 22 publications
51
467
12
24
Order By: Relevance
“…Moreover, the expression of CRP in adipose tissue is regulated by adiponectin. 34 The present study demonstrates that preoperative levels of CRP were predictive for the changes in adiponectin even after adjustment for sex, age, BMI, changes in BMI and preoperative impaired glucose metabolism (Figure 1). These data further support the supposed relationship between hypoadiponectinemia and low-grade chronic inflammation, closely related to increased hs-CRP levels.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, the expression of CRP in adipose tissue is regulated by adiponectin. 34 The present study demonstrates that preoperative levels of CRP were predictive for the changes in adiponectin even after adjustment for sex, age, BMI, changes in BMI and preoperative impaired glucose metabolism (Figure 1). These data further support the supposed relationship between hypoadiponectinemia and low-grade chronic inflammation, closely related to increased hs-CRP levels.…”
Section: Discussionmentioning
confidence: 51%
“…The anti-inflammatory function of adiponectin may prevent atherogenic cell phenomena, such as monocyte adhesion to endothelial cells, differentiation of monocytes to macrophages and, finally, foam cell formation. 35 Current studies have shown that adiponectin also induces various anti-inflammatory cytokines, such as interleukin-10 (IL-10) or IL-1 receptor antagonists, and IL-10 is a biomarker for risk in acute coronary syndrome. 36 Acute coronary syndrome determines the prognosis of cardiovascular disease, in which plaque vulnerability is the important determinant of plaque rupture.…”
Section: Fat Topography Y Matsuzawamentioning
confidence: 99%
“…The significant inverse relationship between adiponectin and CRP confirms other recent smaller studies reporting an inverse relationship between adiponectin and CRP independent of adiposity in non-diabetics. 21,30,31 Studies that have reported inverse associations between IL-6 and adiponectin have generally been carried out in obese subjects, 31,47 and the association of IL6 with adiponectin, which was dependent on adiposity in Abbreviation: CHD; coronary heart disease. Geometric mean adiponectin levels are shown.…”
Section: Associations Of Adiponectin With Metabolic and Vascular Riskmentioning
confidence: 99%
“…2,24 In population-based studies, adiponectin is inversely associated with body mass index (BMI), insulin resistance, triglycerides, and positively associated with high-density lipoprotein (HDL)-cholesterol, components of the metabolic syndrome. [25][26][27][28][29] Although adiponectin has been associated with markers of inflammation in particular, C-reactive protein (CRP) 30,31 associations with other proinflammatory cytokines such as interleukin 6 (IL-6) however have been less consistent 31 and based on small selected populations. Moreover, whether the potential anti-inflammatory properties of adiponectin are mediated by its effect on insulin resistance remains unknown.…”
Section: Introductionmentioning
confidence: 99%